2017
DOI: 10.1002/2016wr019693
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐discharge relationships in headwater streams of the Sierra Nevada, California

Abstract: We examined stream water concentration‐discharge relationships for eight small, forest watersheds ranging in elevation from 1485 to 2465 m in the southern Sierra Nevada. These headwater streams revealed nearly chemostatic behavior by current definitions for K+, Ca2+, Mg2+, Na+, Cl–, and SO42– in most cases but not for NH4+, NO3–, or ortho‐P. The latter ions were somewhat enriched during high flows. All ions studied showed a dilution process at lower flows (<50 L s−1) with the concentration‐discharge relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
46
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 29 publications
(49 reference statements)
11
46
2
Order By: Relevance
“…The C‐Q plots for Ca 2+ at the mid and upper and Na + at the upper flumes show a slight, though non‐significant dilution tendency. Overall, the abundance of strong dilution patterns (| b | > 0.2, except for Mg 2+ at upper flume where | b | = 0.1) at our site, contrast with findings by Godsey et al (), Hunsaker and Johnson (), and Kim et al (), who broadly observed base cations to have chemostatic or negative C‐Q relationships with slopes close to 0 (| b | < 0.1). In the Honeysuckle Creek watershed and across the local landscape, these major cations are present in the glacial parent materials and in soil exchangeable pools (Adams & Boyle, , ; Jin, Williams, Szramek, Walter, & Hamilton, ; Nave, Gough, Le Moine, & Nadelhoffer, ; Williams et al, ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The C‐Q plots for Ca 2+ at the mid and upper and Na + at the upper flumes show a slight, though non‐significant dilution tendency. Overall, the abundance of strong dilution patterns (| b | > 0.2, except for Mg 2+ at upper flume where | b | = 0.1) at our site, contrast with findings by Godsey et al (), Hunsaker and Johnson (), and Kim et al (), who broadly observed base cations to have chemostatic or negative C‐Q relationships with slopes close to 0 (| b | < 0.1). In the Honeysuckle Creek watershed and across the local landscape, these major cations are present in the glacial parent materials and in soil exchangeable pools (Adams & Boyle, , ; Jin, Williams, Szramek, Walter, & Hamilton, ; Nave, Gough, Le Moine, & Nadelhoffer, ; Williams et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Although other researchers have found that many of the analytes they measured displayed chemostatic behaviour and had flat C‐Q shapes with slopes below | b | < 0.2 (Basu et al, ; Godsey et al, ; Hunsaker & Johnson, ; Kim, Dietrich, Thurnhoffer, Bishop, & Fung, ; Thompson et al, ), we found that all positive and negative Honeysuckle Creek C‐Q relationships, with the exception of Mg 2+ at the upper flume, were strongly significant with slopes greater than | b | > 0.2. Our results did generally agree with the findings of these researchers that solute concentrations vary less than discharge.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations